Assessment of Agro-morphological Performances of 56 Accessionsof Pennisetum glaucum with Grain and Fodder Potentials in Niger - Moussa, Hamadou; KINDOMIHOU, Valentin; HOUEHANOU, Thierry Dèhouégnon; Chaibou, Mahamadou; Souleymane, Oumarou; Soumana, Idrissa; ISSA, SALISSOU; Issaka, Ahmadou; Issoufou, Kassari Ango; DOSSOU, JOSEPH; Houndonougbo, Frédéric; BABATOUNDE, SÉVÉRIN; et al. (My University, 2020)
Morphological characterization is the ﬁrst step instudying the genetic diversity of cultivated plants. Thepresent study examined agro-morphological performanceof the pearl millet local accessions collected across theNiger country, aimed to: (a) characterize, (b) discriminatemorphologically the pearl millet accessions groups and(c) identify the pearl millet genotypes with promising grainand fodder potential. Fifty-six pearl millet accessions col-lected in the eight Niger regions (Agadez, Diffa, Dosso,Niamey, Tahoua, Tillabe´ry and Zinde r) were evaluated inan Alpha lattice design with 3 replicates in Djirataoua andKollo localities. Twenty-ﬁve speciﬁc agro-morphologicaldescriptors were used for this purpose. The data set was submitted to descriptive analyses and indicated wide sig-niﬁcant accessions diversity. Hierarchical cluster analysisrevealed 5 phenotypic groups, and principal componentanalysis showed 3 components representing 60.45% oftotal variability. Canonical discriminant analysis indicated20 major traits of the discriminated phenotypic groups.Group G1holds early accessions, with average perfor-mances in grain production and low performances in bio-mass production. Group G2holds early accessions, withgood performances for grain production and fodder bio-mass. Group G3holds early–late accessions with goodgrain performances and low fodder performances. G4holdsboth early and late accessions with good fodder perfor-mance and good grain performance. Finally, G5includesboth late accessi ons with better fodder performances andbad grain performances. These groups can be used asparents in the creation of improved varieties for better grainand fodder production performance. Otherwise, Djirataouawould be ideal for the tested accessions to express theiragro-morphological potentials
Keywords: Agro-morphological traits  Diversity Fodder  Grain  Accessions  Millet  Nige